Literary experimentations: reading practices and artistic experiences in schools (Olhar de Professor, 2021)
This study analyzes pedagogical activities that prioritize reading practices in schools, by doing book exchange, group reading, artistic experiences and shared reading with children and university students, in a research and extension project at the public schools. The focus of this analysis are the reading practices and the aspects related to their use, regarding the shapes, the objects, the tools and the aims of the reading process. For this reason, not only “reading protocols” (Chartier, 1996) and as “significations plurielles et mobiles” (Chartier, 2002a). The theoretical and methodological approach used admits that reading practices produce senses and make the body interact with the book, with itself and with other people, which means those practices produce body positions that occupy space and practices related to cultural components.
Keywords: Books. Reading. Literary experimentation.